Omagua resurgence Ethnocide, ethnogenesis and cultural resource of an invisible group - Cabrero Miret, Fernando Martin (2020)
A culture called “Omagua”, among other names, was described as one of the most numerous cultures of the Amazonian past in the first chronicles of the European discovery of the Amazon (sixteenth and seventeenth centuries). They also appear, more definedly, in the Jesuit journals of the Mayna missions (from second half of the 17th to the end of the 18th century). Despite the impact of these reductions and European colonization, the Enlightened, travellers, and officials of the eighteenth and nineteenth centuries still cite the Omaguas or Kambebas (their name in Brazil) as a proud group, reminiscent of their position as “lords” of the river. In the early twentieth century, between the 1930s and 1950s, they were recorded ethnographically in and around Iquitos (Peru), when their geographical marginalization, population decline, and virtually cultural extinction are evident. Do they continue to exist in the early 21st century? This article reviews the ethnographic literature of the twentieth century concerning this people, and exposes the results of the field work carried out in early 2014 in territory once inhabited by the Omaguas, making a comparison between three countries with a different sociocultural dynamic: Peru (ethnocide), Brazil (ethnogenesis), and Ecuador (cultural resource).